Visible Spectrophotometric Determination of Ornidazole from Bulk Drug and Formulations - S. Sarsambi, Prakash; Appala Raju, S. (Asian Journal of Chemistry, 2010)
A simple spectrophotometric method for the determination of ornidazole is developed. This method is based on the formation of green coloured species with 3-methyl-2-benzothialzolinone hydrazone (MBTH) in presence of FeCl3, exhibiting maximum absorption at 623 nm. Beer's law was obeyed in the concentration range of 2 to 10 mcg/mL. The results of analysis of the proposed method have been validated statistically and by recovery study. The proposed method is selective, simple and economical for the determination of ornidazole.